Bioremediation of oil contaminated soil using biosurfactant produced by Pseudomonas aeruginosa - Pradeep NV; Anupama; Anitha G; Renukamma; Sudhakar Avvaru; Afreen SS (Journal of Research in Biology, 2012)
Biosurfactants are surfactants that are biologically produced from bacteria, yeasts and fungi. Examples include Pseudomonas aeruginosa which produce biosurfactants from various substrates including sugars, oil and wastes. Biosurfactants have the property of reducing surface and interfacial tension. These are biodegradable and nontoxic. In the present study saw dust and rice husk were used as substrates for biosurfactant production. Pseudomonas aeruginosa was isolated from contaminated soil sample collected from diesel contaminated site for the production of Biosurfactant. The fermentative production of biosurfactant from Pseudomonas aeruginosa was carried out by solid state fermentation (SSF) using two low cost substrates (rice husk and saw dust). These substrates were inoculated with P. aeruginosa and surface tension was measured on 1st, 3rd, 5th, 7th and 9th day. The highest reduction of surface tension (22.9 mN/m) was obtained using saw dust on 7th day. Produced biosurfactant have been tested for remediation of oil contaminated soil. The contaminated soil was prepared in the laboratory by mixing oil, sand and seed (diesel contaminated soil) in the ratio of 10:2:1. Contaminated soil was further transferred to containers and was allowed for acclimatization. Three containers were used in this study 1) Containing contaminated soil without biosurfactant (C1). 2) Container containing contaminated soil with 4 g of biosurfactant per kg of soil (C2). 3) Containing contaminated soil with 8 g biosurfactant per kg of soil (C3). The oil remaining in soil was determined by solvent extraction method using n-hexane. Oil removal was high in the C2 container which contained 4 g of biosurfactant per kg of soil.